A short version of the nurse professional competence scale for measuring nurses' self-reported competence. (December 2018) - Nilsson, Jan; Engström, Maria; Florin, Jan; Gardulf, Ann; Carlsson, Marianne
Abstract: Background: The Nurse Professional Competence (NPC) Scale with 88-items has been used to measure self-reported competence among nursing students and registered nurses in many national and international nursing research projects. However, a shorter version of the scale with maintained quality has been requested to further enhance its usability. Objectives: To develop and evaluate the construct validity and internal consistency of a shorter version of the NPC Scale. Design: A developmental and methodological design. Participants and Settings: The study was based on a sample of 1810 nursing students at the point of graduation from 12 universities in Sweden. Methods: The number of items in the original NPC Scale was reduced using several established research steps and then evaluated for data quality and construct validity using principal component analysis and confirmatory factor analysis. Reliability was measured as internal consistency using Cronbach's alpha. Results: The extensive process of reducing the number of items resulted in a version with 35 items. Principal component analysis resulted in six factors explaining 53.6% of the variance: " Nursing Care ", " Value - based Nursing Care ", " Medical and Technical Care ", " Care Pedagogics ", " Documentation and Administration of Nursing Care ", and " Development, Leadership, and Organization of Nursing Care ". All factors showed Cronbach's alpha values of >0.70. The confirmative factor analysis goodness-of-fit indexes were for root mean square error of approximation 0.05 and for comparative fit index 0.89. Conclusions: The NPC Scale Short Form (NPC Scale-SF) 35-items revealed promising results with a six-factor structure explaining 53.6% of the total variance. This 35-item scale can be an asset when used alone and together with other instruments it can provide the possibility of more complex analyses of self-reported competence among nursing students and registered nurses.